Q: What is (4w plus 2w)2?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

given: 4w+(6k-3w)+(2-k)remove parentheses: 4w+6k-3w+2-kcollect like terms: 4w-3w+6k-k+2simplify: w+5k+2

It is 10w + 4.

Let's define some variables. We'll call the length L, and the width W. Then we can express the above algebraically:300 (perimeter) = 2L + 2W3600 (area) = L x WNow let's find one variable in terms of the other:300 = 2L + 2W300 - 2W = 2L(300 - 2W)/2 = LSince we now have the length in terms of width, we can substitute for L in the second equation:3600 = L x W3600 = [(300 - 2W)/2] x W3600 = (300W - 2W2)/27200 = 300W - 2W2---- That was part one of the solution. Now we have to reformat the equation and use the quadratic formula (for the formula and syntax, visit the Wikianswers link below):-2W2 + 300W - 7,200 = 0W = [-300+or-(3002 - 4(-2)(-7,200)1/2]/[2(-2)]W = [-300+or-(90,000 - 57,600)1/2]/-4W = [-300+or-(32,400)1/2]/-4W = (-300 + or - 180)/-4Quadratic equations usually have two answers, since they are parabolas and will most likely cross the x-axis twice.The first answer is:w = (-300 + (-180))/-4W = -480/-4W = 120(L = 30)Or the second answer:W = (-300 - (-180))/-4W = (-120)/-4W = 30(L = 120)Either way, the dimensions of the plot must be 120 ft by 30 ft

2w2 - 19w

(w+5)(4w+2) - 270 = (4w)(w) 4w2 + 22w + 10 - 270 = 4w2 22w = 260 w = 11.81818181 Length = 4w = 47.2727 or 47 3/11 Width = 11.8181 or 11 9/11

Related questions

That doesn't factor neatly. Applying the quadratic equation, we find two real solutions:(3 plus or minus 3 times the square root of 33) divided by 4w = 5.0584219849035215w = -3.5584219849035215

(2w + 3)(w + 5)

(x+5)(2x+3)

given: 4w+(6k-3w)+(2-k)remove parentheses: 4w+6k-3w+2-kcollect like terms: 4w-3w+6k-k+2simplify: w+5k+2

It is 10w + 4.

2w-6w+9 -4w+9 the coefficient of -4w is -4

11 + 5w

It is: 6w-2

It is: 5+4w simplified

w + 3 = 4w - 6 9 = 3w w = 3

3/4w+8=1/3-712(3/4w+8)=12(1/3w-7)9w+96=4w-849w-4w+96=4w-4w-845w+96=-845w+96-96=-84-965w=-1805w/5=-180/5w=-36

Let's see if I can answer this. 4X + 6Y + 3Y + 4W + 6X - 7W = (4 + 6)X + (6 + 3)Y + (4 - 7)W = 10X + 9Y - 3W